The polarity of war metaphors in sports news: a corpus-informed analysis - Tan, Kim Hua; Hamdi Khalis; Nur-Ehsan Mohd-Said; Ong, Song Howe (Penerbit Universiti Kebangsaan Malaysia, 2021)
War metaphors have long been used in sports news reporting. In reality, war metaphors are also used commonly in daily conversations. The wide usage of war metaphors in sports news reporting is because the two domains (i.e. war and sports) are comparable to each other, thereby enabling the use of war terms to describe the sports domain. Following a corpus-informed approach, the strength of modifiers (adjectives) in reversing or retaining the polarity of war metaphors and subsequently affecting news sentiment was examined. Sports news from the BBC Sports News, Malay Mail Online and the Malaysian Online Sports News Corpus, which amounted to 2.3 million words of sports texts, were subjected to corpus analysis. The UCREL Semantic Analysis System identified possible war terms in the corpora and Collocate 2.0 was used to locate adjectives and their respective collocates. Findings indicated that news writers do not necessarily use adjectives as a tool to negate the positive sentiment of news or intensify the negative sentiments. Instead, war metaphors collocated with particular modifiers resulted in a good balance of sports news reported with a negative polarity, positive polarity or a neutral tone.